ANALYSIS PROGRAM BUSSINESS DEVELOPMENT SERVICES (BDS) AND EXPANSION OF NETWORK PERFORMANCE MANAGEMENT PRODUCT MARKET FOR SMALL AND MEDIUM ENTERPRISES (UKM) IN THE REGION GERBANGKERTOSUSILA - Priyono; Suci, Rahayu Puji; Mahargiono, Pontjo Bambang (European Scientific Journal, ESJ, 2013)
Some program development support system for cooperative effort, Micro, Small And Medium aims to simplify, accelerate and broaden access Cooperatives, Micro, Small and Medium Enterprises to productive resources to be able to take advantage of the opportunities and potential of local resources to develop KUMKM businesses, as well as adjustment scale its business to be more efficient. Results if the data using the method of AHP and expert choice software assistance to the respondents’ answers on a variety of criteria that affect the Program Business Development Services (BDS) Against management Performance Network Expansion Markets And Products For Small and Medium Enterprises (UKM) in Region Gerbangkertosusila.